Comparison of early- and late-onset NMOSD-related optic neuritis in THAI patients: Clinical characteristics and long-term visual outcomes - Watcharaporn Thongmee (2022)
Objective: To compare demographic data, clinical and radiological characteristics, treatments, and long-term visual outcomes between patients with late-onset neuromyelitis optica spectrum disorder-related optic neuritis (LO-NMOSD-ON) (age at onset ≥ 50 years) and patients with early-onset neuromyelitis optica spectrum disorder-related optic neuritis (EO-NMOSD-ON) (age at onset < 50 years). Patients and Methods: This retrospective study included 47 patients (69 eyes) who were diagnosed with neuromyelitis optica spectrum disorder-related optic neuritis (NMOSD-ON) over a 12-year period. There were 14 patients (21 eyes) and 33 patients (48 eyes) in the LO-NMOSD-ON and EO-NMOSD-ON groups, respectively. Results: LO-NMOSD-ON-affected eyes exhibited significantly worse median nadir visual acuity (VA) at optic neuritis (ON) onset, compared with EO-NMOSD-ON-affected eyes (2.7 logMAR (range 2.6-2.9 logMAR) vs 1.95 logMAR (range 0.4-2.9 logMAR); p = 0.03). Similarly, 100% of LO-NMOSD-ON-affected eyes demonstrated a nadir VA of worse than or equal to 1.0 logMAR, compared with 62.5% of EO-NMOSD-ON-affected eyes (p = 0.03). LO-NMOSD-ON-affected eyes had a worse median final VA, compared with EO-NMOSD-ON- affected eyes (1.3 logMAR (range 0-2.9 logMAR) vs 0.3 logMAR (range 0-2.9 logMAR); adjusted p = 0.037). LO-NMOSD-ON-affected eyes more frequently exhibited a final VA of worse than or equal to 1.0 logMAR, compared with EO-NMOSD-ON-affected eyes (57.1% vs 27.0%; adjusted p = 0.039). A positive correlation was observed between age at ON onset of each eye and the final VA (logMAR) (Spearman r = 0.34, p = 0.0075). The remaining parameters did not significantly differ between the two groups. Conclusion: Patients with LO-NMOSD-ON had significantly worse nadir VA at ON onset and significantly worse final VA, relative to patients with EO-NMOSD-ON. Age at ON onset of each eye was positively correlated with final VA (logMAR). Despite the difference in common age at onset, NMOSD-ON should be included in the differential diagnosis of late-onset acute to subacute optic neuropathy, along with ischemic optic neuropathy.